2019
DOI: 10.1016/j.simpat.2019.101933
|View full text |Cite
|
Sign up to set email alerts
|

An E2E simulator for 5G NR networks

Abstract: As the specification of the new 5G NR standard proceeds inside 3GPP, the availability of a versatile, full-stack, End-to-End (E2E), and open source simulator becomes a necessity to extract insights from the recently approved 3GPP specifications. This paper presents an extension to ns-3, a well-known discrete-event network simulator, to support the NR Radio Access Network. The present work describes the design and implementation choices at the MAC and PHY layers, and it discusses a technical solution for managi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(81 citation statements)
references
References 16 publications
0
77
0
4
Order By: Relevance
“…This paper presented Simu5G, a new model library for 5G NR for the OMNeT++ simulation framework. To the best of our knowledge, this is one of two libraries allowing end-to-end application-level communications in complex, heterogeneous scenario (the other one being 5G-LENA [5]), but the only one modelling ENDC deployments, FDD access, D2D communications, MEC and C-V2X. We have described Simu5G's resource management and protocol layers, to allow prospective users to understand its modeling philosophy, aimed at research on 5G services and 5G resource management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper presented Simu5G, a new model library for 5G NR for the OMNeT++ simulation framework. To the best of our knowledge, this is one of two libraries allowing end-to-end application-level communications in complex, heterogeneous scenario (the other one being 5G-LENA [5]), but the only one modelling ENDC deployments, FDD access, D2D communications, MEC and C-V2X. We have described Simu5G's resource management and protocol layers, to allow prospective users to understand its modeling philosophy, aimed at research on 5G services and 5G resource management.…”
Section: Discussionmentioning
confidence: 99%
“…Among end-to-end simulators of 5G networks, we find 5G-LENA [5] and the 5G-air-simulator [6], both recently released. The 5G-LENA model library for the ns3 framework evolves from the LENA 4G library [7] and includes an upgraded, standard-compliant version of the ns3 mm-wave module [8].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the popular and open source ns-3 simulator provides the perfect framework for reproducible research and collaborative development, as it was already demonstrated in [28], and disposes of multi-RAT models. Notably, the ns-3 simulator has recently released novel models for NR Release-15 [30], [31] and IEEE 802.11ad [32], [33].…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the present work is extremely timely and relevant since 3GPP has not started yet the related Work Item, which is scheduled for Release-17 [19], [20]. To develop NR-U, we have extended the NR Release-15 model in [30] by incorporating new functionalities to allow operation in unlicensed bands, while fulfilling its regulatory requirements, in terms of LBT, maximum Channel Occupancy Time (COT), minimum Occupied Channel Bandwidth (OCB), and maximum power limits. The code is freely available from [34] under the GPLv2 license.…”
Section: Introductionmentioning
confidence: 99%